SYNTHESIS, CHARACTERIZATION AND BIOACTIVITY EVALUATION OF Mn(II), Co(II), Ni(II) AND Cu(II)-QUERCETIN COMPLEXES: ANTIMICROBIAL, ANTIOXIDANT AND CYTOTOXICITY PROPERTIES - Mukhtar, Haruna; Habu, Nuhu Aliyu; Musbahu, Yahaya (FUDMA Journal of Sciences, 2025)
In this study, metal (II)- quercetin complexes are synthesized and characterized by using FT-IR, water of hydration, conductivity, magnetic susceptibility and elemental analysis. The metal(II) complexes of manganese,  cobalt, nickel, and copper with the ligand were synthesized by refluxing respective metal ions with the corresponding ligand in a 1:2 mole ratio. The FT-IR spectra of the quercetin showed a broad band at 3248 cm-1, assignable to phenolic (OH) stretching vibrations. Another sharp absorbance band seen at 1666 cm-1 assigned to aromatic C=O stretch in the ligands were shifted to lower frequency range of 1596 – 1633 cm-1, suggesting coordination through oxygen of the C=O of the ligands respectively. New bands at the lower region in the range of 530 – 616 cm-1 which were not observed in the ligand, further confirmed M–O chelation in the complexes, which confirmed the deprotonation of phenolic (OH) in the ligands.  Molar conductivity values obtained for the complexes were found to be low (5.18 – 11.00 Ω -1 cm2mol-1) indicating non-electrolytic nature. Magnetic moments determined were in the range 1.69 – 5.92 BM, indicating that all the complexes are paramagnetic suggesting a tetrahedral geometry for the complexes. The relative percentages of the constituent elements from CHN analysis showed strong agreement with theoretical percentages for all the respective complexes. The antimicrobial activity of quercetin and its complexes was evaluated using the well diffusion method against three bacterial and fungal isolates each.
Keywords: Cytotoxicity; Quercetin; Bacterial; Antifungal; Microorganisms